Emerging trends and applications in cognitive computing - Mallick, Pradeep Kumar, 1984-; Borah, Samarjeet (Engineering Science Reference, 2019)
"This book brings together the latest research in computer science: cognition computer science, cognitive science, intelligence science, information sciences and machine intelligence. It also extends the information management capacity of individuals through the development and application of novel concepts in human-system integration to address cognitive bottlenecks (limitations in attention, memory, learning, comprehension, visualization abilities, and decision making)"--